Outcome of Husband-to-Wife Kidney Transplantation With Mutual Children: Single Center Experience Using T Cell-Depleting Induction and Review of the Literature - Senn, Lisa; Wehmeier, Caroline; Hönger, Gideon; Geiger, Irene; Amico, Patrizia; Hirt-Minkowski, Patricia; Steiger, Jürg; Dickenmann, Michael; Schaub, Stefan (Frontiers in Medicine, 2021)
Few data on husband-to-wife transplantations with mutual children (H2W) exist in the current era. We investigated the outcome of H2W transplantations (n=25) treated with T cell-depleting induction compared to women with prior pregnancies also receiving their first HLA-mismatched kidney transplant, but from a different donor source: (i) other living donor (n=52) and (ii) deceased donor (n=120). Seventy-four percent of the women had ≥2 pregnancies; median follow-up time was 5 years. Death-censored allograft survival was significantly lower in the H2W group compared to the other two groups (p=0.03). Three of four graft losses in the H2W group were due to rejection. 5-year patient survival in the H2W group was high and similar compared to the other living donor group (100% vs 98%; p=0.28). The incidence of (sub)clinical antibody-mediated rejection was higher in the H2W group (36% vs 20% vs 18%) (p=0.10). The frequency of infections was similar among the three groups. No immunological parameter was predictive for rejection or graft loss in H2W transplantations. In conclusion, H2W transplantation is a valuable option, but associated with a higher risk for allograft loss due to rejection despite T cell-depleting induction. Further research is required for better risk prediction on an individual patient level.